A London residential retrofit case study: Evaluating passive mitigation methods of reducing risk to overheating through the use of solar shading combined with night-time ventilation. (July 2019) - Grussa, Zoe De; Andrews, Deborah; Lowry, Gordon; Newton, Elizabeth J; Yiakoumetti, Kika; Chalk, Andrew; Bush, David
Overheating in the indoor environment, specifically in domestic homes, schools and healthcare settings has become of great concern to us in the UK. This is due to frequent hot weather events as a result of the continually rising global average temperatures. Overheating is a result of the heat gains associated with occupancy and solar heat gains trapped in the internal environment. The continuing rise in global average temperatures and improved insulation standards necessary to mitigate heat losses during the winter, in conjunction with poorly planned ventilation strategies, are exacerbating overheating during warmer weather conditions. In the last decade, there has been a considerable improvement in reducing heat gains associated with occupancy (from lighting and equipment), thus making solar heat gains more prominent in contributing to overheating. With the rise in the number of buildings that overheat and the rise in the number of associated deaths these contribute to, it is now crucial that passive measures are utilised appropriately, and for building occupants to be educated in how to safeguard their homes against overheating. This research is centred around a real-world monitoring case study and investigates how the proposed passive measures can mitigate overheating risk. These measures include the use of different internal and external solar shading devices combined with a night-time natural ventilation strategy. This study was conducted in a south-west facing, single aspect retrofit apartment building in London between August and October 2016 and 10-min interval data were collected during the daytime over 20 days. Throughout the monitoring period, a controlled window opening strategy was applied in rooms where differing shading strategies were implemented. In the absence of night-time measurements, the rooms were evaluated according to CIBSE TM52 Overheating Criteria to assess the frequency and the severity of overheating and mitigation methods were statistically compared to analyse the difference in internal operative temperature increase according to the type of passive mitigation scenario implemented. The combination of opening windows at night and the closure of shading devices during the day can provide a significant thermal benefit to occupants. The inter-relationship between glazing, shading, ventilation amongst other variables needs to be collectively evaluated at the building design stage to ensure the appropriate design of an effective façade management strategy. Practical application : This study aims to add to the body of knowledge surrounding overheating by investigating the impact that the combination of shading and night-time ventilation strategies can have on a newly refitted, urban apartment. It demonstrates how the frequency, severity and the absolute maximum temperature can be identified using existing industry criteria and then uses this methodology alongside inferential statistics to compare the effectiveness of differing shading strategies when combined with night purge ventilation.